A review of natural polysaccharides for food cryoprotection: Ice crystals inhibition and cryo-stabilization. (May 2022) - Sun, Xianbao; Wu, Yan; Song, Zibo; Chen, Xiangyu
Abstract: Although freezing is by far the most common method of food preservation, deteriorative changes in food quality are inevitable because of the formation of ice crystals and other physicochemical reactions. In recent years, cryoprotective agents from natural sources have attracted great interest and been applied to the frozen food industry to overcome freezing damage. Natural polysaccharides have been proved to inhibit ice crystals formation. They possess cryo-stabilized effects due to their rheological properties and antioxidant activity, thus showing great potential in food to achieve the desired cryoprotection levels. In this review, we first summarized the quality damage of food during freezing and frozen storage. Next, the effects of natural polysaccharides on the formation of ice crystals were discussed from the three aspects of ice nucleation, growth, and ice recrystallization. The review focused on the action mechanism of polysaccharides on ice recrystallization inhibition (IRI), in which the polysaccharide-ice interaction and the water perturbation by hydration of polysaccharides might play critical roles in the IRI. Moreover, the cryo-stabilized effects of polysaccharides on food systems were discussed. This review is expected to shed new light on the antifreeze mechanism of natural polysaccharides, inspiring further research into exploring and applying new polysaccharide resources for food cryoprotection.